UUM, UiTM, hospital hold blood donation campaign - New Sunday, Tribune (New Sunday Tribune, 2013)
MUKAH: A blood donation campaign theme 'Help save a life, give the gift of blood' was successfully held at Universiti Teknologi MARA Sarawak (UiTM) Mukah Campus, here, yesterday morning.